Solitary Skull Metastasis as Initial Manifestation of Hepatocellular Carcinoma – A Case Report - MN, Ellyda; A, Mohd Shafie (IIUM Medical Journal Malaysia, 2009)
Metastatic spread of tumors to the skull is quite unusual and often represents diagnostic and therapeutic issues. Skull involvement can be observed in various neoplasms of epithelial origin and are most often due to lung, breast, thyroid, kidney and prostate cancers. However, skull metastases from hepatocellular carcinoma (HCC) have been rarely reported. The prognosis for patients with hepatocellular carcinoma is so poor that treatment of such distant metastatic lesion cannot be achieved before death occurs due to the primary malignancy. Therefore, the clinical manifestations of cranial metastasis prior to that of primary hepatocellular carcinoma have rarely been reported. This case illustrates a rare case of skull metastasis as an initial manifestation of hepatocellular carcinoma. Although a solitary skull metastasis prior to the diagnosis of HCC demonstrates rare metastatic behavior for HCC, especially in Asia, skull metastases from HCC should be included in the differential diagnosis of skull tumors, even if the patient is asymptomatic of liver cirrhosis.